The Effect of Application of Tax Amnesty on Taxpayer Compliance - Madjid, Suhirman; Asaari, Masagus (Research of Accounting and Governance, 2023)
This study aims to determine and compare taxpayer compliance before and after the Tax Amnesty by using the Paired Sample t-test. The population of this study is individual taxpayers participating in Tax Amnesty in the surrounding areas of DKI Jakarta. Sampling used the accidental sampling method. Based on this method, a sample of 552 WPOP was obtained. The data used are primary data with a survey method using questionnaire media. The results of the study show that there is an effect of Tax Amnesty on taxpayer compliance. The results of this study can be used as a reference in implementing the Tax Amnesty that will be applied later. Must taxes should take advantage of the policy Tax Amnesty by reporting assets and liabilities honestly to the Director General of Taxes so you will not be fined or tax penalties. In this case, the supervisory function of the Director General of Taxes should be maximized so Taxpayer compliance in any reporting year is improved